La aplicación de la figura jurídica de cooperación eficaz, sus beneficios y requisitos de procedibilidad en las Unidades de Garantías Penales del cantón Quito, año 2022. - Hidalgo Villalba Herlinda Narcisa (2024)
Organized crime is a phenomenon that directly affects the entire State and prevents society from living together in an environment of peace. These criminal structures are characterized by generating panic with the aim of developing their illicit activities and accumulating illicit assets. Ecuadorian legislation has established the figure of effective cooperation in its criminal regulations in order to appease the problem, a legal institution that is aimed at combating organized crime groups through the cooperation of one of its members and even of themselves. leaders of these organizations. The research carried out is carried out under the mixed approach, thus managing to collect qualitative and quantitative data that allow for an in-depth analysis of the topic raised. As a result of the research, it is obtained that the procedural requirements established in the figure of effective cooperation are aimed at combating the organized crime and prevent its proliferation. Keywords: Effective cooperation, Organized crime, Impunity, Procedure, Legal security.